Changes in anthocyanin, total phenolic, antioxidant activity, texture and color of canned strawberry during storage - Naseem, Zahida; Gull, Amir; Wani, Sajad Mohd; Masoodi, Farooq Ahmad; Ganaie, Tariq Ahmad (Journal of Postharvest Technology, 2017)
In the present study, strawberry at three different stages (unripe, half ripe and full ripe) were canned.Physico-chemical, ascorbic acid, color;  texture and phytochemical analysis were carried out for canned strawberry. Results showed decrease in moisture content 59.96-56.89%,  62.74-57.01%, 56.96-50.92% and titratable acidity 2.32-0.20%, 1.06-0.11%, 0.74-0.09% respectively. Significant (p≤0.05) decrease in  anthocyanin, total phenolic content, antioxidant activity, texture and color L* and a* value were also observed. However significant (p≤0.05)  increase in total soluble solids from 32.0-37.11,34.0-37.06, 39.0-40.13%,ascorbic acid content 1.57-4.11,1.43-2.82, 1.37-1.81% and color b*  value 27.17-56.03, 27.96-57.58, 33.29-50.86 respectively was noticed during storage period.
Keywords: Canned strawberry; ascorbic acid; anthocyanin; total phenolic content; quality